Traumatic Brain Injury - Nelasari, Diamond; Sumandari, Astri; Sasmitha Ajiningrum, Ridha (Jurnal KESANS : Kesehatan dan Sains, 2022)
Traumatic brain injury (TBI) is an injury to the brain that is non-degenerative and non-congenital but is caused by external mechanical forces that can cause a decrease in consciousness and temporary or permanent disturbances in cognitive, physical, and psychosocial functions. The latest data from the CDC in 2014 there were as many as 2.87 million people in the world suffered head injuries. Certain segments of society that are at high risk for TBI include young people, low-income individuals, unmarried individuals, members of ethnic minority groups, male gender, urban dwellers, substance abusers, and people with previous TBI. Keywords: Head Trauma, Traumatic Brain Injury, Radiology